Impulsive Buying in TikTok Live Streaming: Enhancing The Role of Telepresence, Brand Trust, and Flow State - Parahiyanti, Cesya Rizkika; Dimara, Noach Iriandi (Universitas Muhammadiyah Magelang, 2024)
Technology has taken a significant role in digital marketing. The presence of live streaming trades has formed a new trend for brands to increase their sales. Telepresence takes a significant role in forming brand trust and flow state which then can drive the audience to do impulsive buying. This research aims to examine the effect of variable telepresence, brand trust, and flow state to impulsive buying on Tiktokshop live streaming activities by EatSambel. The population in this research the users of Tiktok application who ever watched the live streaming of EatSambel with 228 samples which is chosen by purposive sampling technique and the data collecting used questionnaires. The research analysis used SEM-PLS which is managed by SmartPLS 3 software. The result of the data showed that telepresence has positively and significantly effect to impulsive buying, brand trust, and flow state. Flow state also has positively and significantly effect towards impulsive buying, while the effect of brand trust to impulsive buying is not significant. These findings provide a practical understanding of the quality of telepresence and interesting interactions in live streaming that can be considered by marketers to increase sales by encouraging impulsive buying behaviour in consumers.